Development of Green Building Concept in Building Gas Station Based on BREEAM With Nzeb Method For Increasing Cost Performance - Abdul Charis; Mawardi Amin; Agus Suroso (Postgraduate, University of Mataram, 2025)
In this case, the rapid development of gas station construction is a significant threat to life and global growth, with greenhouse gas (GHG) emissions functioning as one of the main catalysts. Indonesia is urged to immediately embrace green concepts in the progress of building construction efforts, including gas station buildings. This is the mission of the Sustainable Development Goals 2030, which states that by 2030, new building concepts will be 100%. Researchers conducted a study to answer questions about the problem, namely the BREEAM-based green concept with the nZEB method. Based on this research, the green building concept will experience an increase in cost ranging from 4.66% to 22.56% with BREEAM assessment compared to conventional design. Implementing BREEAM using the nZEB method reduced cost from 3.03% to 10.72%. The results of this research revealed ten factors that influence the cost performance of the BREEAM-based Green Building Gas Station Building project with nZEB, namely: reduction of energy use and carbon emissions, indoor air quality, waterproof performance, monitoring water use, heating for each comfort space, energy-efficient transport systems, transport assessment and travel planning, water leak detection, water-saving equipment, and sustainable transport measures. This research also found the implementation of BREEAM using the nZEB method.